Quality Assessment of Banana Juice and Beer in Rwanda - Kanyana, I.; Ouma, Emily A.; Asten, Piet J.A. van (Science Alert, 2013)
Banana juice and beer samples were collected at different points along the processing and marketing chain from four localities in Rwanda and analyzed for microbiological and physico-chemical quality by adapting a Hazard Analysis and Critical Control Points (HACCP) methodology. The results showed high total bacterial counts of 9.02-9.86 log10 cfu mL-1 with yeast and moulds as well as lactic acid bacteria being the predominant microbes. Coliform counts were high in artisanal processed banana beer, 7.65-8.11 log10 cfu mL-1 but were low or undetected in semi-industrial processed beer samples. The presence of coliforms in the artisanal processed banana beer indicated post-fermentation contamination. High total bacteria and coliform counts were associated with samples from artisanal processors, those drawn from plastic non-food grade containers and diluted with water indicating these as potential critical points for microbial ingress.